Performance Analysis of Bipolar Optical Code Division Multiple Access with Dual Electro-Optical Modulator Scheme for Free-Space Optical Communication - Eddy Wijanto (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2021)
In this study, the performance of bipolar optical code division multiple access (OCDMA) with dual electro-optical modulator (EOM) scheme for multi-user scenario was tested and analyzed with OptiSystem version 10. The performance measurement was implemented for free-space optical (FSO) communication and includes the common noises in optical communication. Two different channels were used in the measurement, i.e., additive white Gaussian noise (AWGN) and fading channel. Two extreme weather conditions, strong rain and storm, were considered in the simulation. The performance between three spectral amplitude coding (SAC) codes, i.e., Modified M-Sequence code, Walsh-Hadamard code, and random diagonal (RD) code were measured and compared. The simulation results indicate that Modified M-Sequence code had the highest BER while RD code achieved the lowest BER in the short-range and Walsh-Hadamard code got the lowest BER for the medium-range of FSO, both for AWGN only and AWGN with fading channel. In strong turbulence condition, the performance of all codes become comparable after 500 m of FSO range. Modified M-Sequence suffered the lowest performance degradation while RD code endured the highest performance deterioration in all-weather condition. The results show that Modified M-Sequence can be applied for medium to long-range FSO.